2019
DOI: 10.1002/lary.27992
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation improves olfactory functions

Abstract: Objectives The aim of this study was to investigate changes in olfactory function after smoking cessation. Methods We conducted a cross‐sectional study involving 28 volunteers who were admitted to the smoking cessation section of our hospital. Olfactory tests were performed immediately before smoking cessation and 45 days after smoking cessation. The duration of smoking and the number of cigarettes smoked per day were noted. Results The mean duration of smoking was 25.5 ± 12 years, and the participants smoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
0
15
0
3
Order By: Relevance
“…Prior studies have found both negative and positive effects of smoking on olfactory function in the general population. 13,14 Although smoking cessation seems to improve both subjective and measured olfactory function, 15,16 the underlying pathogenesis linking olfactory dysfunction and smoking is not clear, and several possible explanations exist. Tobacco smoke exposure may cause increased apoptosis in olfactory neurons, which can overwhelm the regenerative capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found both negative and positive effects of smoking on olfactory function in the general population. 13,14 Although smoking cessation seems to improve both subjective and measured olfactory function, 15,16 the underlying pathogenesis linking olfactory dysfunction and smoking is not clear, and several possible explanations exist. Tobacco smoke exposure may cause increased apoptosis in olfactory neurons, which can overwhelm the regenerative capacity.…”
Section: Introductionmentioning
confidence: 99%
“…They hypothesized that insufficient regeneration of olfactory epithelium was responsible for the lack of improvement in the odor threshold score. 9 Tobacco smoke has been proven to be harmful to cognitive function in studies. 30,31 It has been established before that there is a connection between olfactory and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…They hypothesized that insufficient regeneration of olfactory epithelium was responsible for the lack of improvement in the odor threshold score. 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations